.NET 2.0 for Delphi Programmers - Shemitz, Jon (Apress : Imprint: Apress, 2006)
.NET 2.0 for Delphi Programmers explores .NET from a Delphi programmers viewpoint, and it is ideal for Delphi programmers moving to .NET. It presents the core concepts of the .NET world in terms you are familiar with. This book will help you with Delphi for .NET as well as C#. Apress publishes migration books for both Visual Basic 6 and C++ programmers moving to .NET. Consider this the Delphi installment of Apress migration books! There is ample coverage of C# as well as Delphi for .NET inside this edition.